Storage quality assessment of a sheet snack produced from liang leaves (Gnetum gnemon var. tenerum) - Pisuchpen, Supachai; Usawakesmanee, Worapong; Siripongvutikorn, Sunisa; Khatcharin, Nicha; Rujirapong, Chanonkarn (Italian Journal of Food Science, 2024)
This study investigates a novel leaf sheet snack from liang, an indigenous vegetable in Southern Thailand. The prepared snack has high protein, fiber, calcium, and vitamins A and B2. Storage conditions and packaging impact its shelf life. Based on the calculation, laminated aluminum foil extended shelf life to 1 year at 30°C and relative humidity (RH) of 60%. Moisture absorption during storage led to physicochemical changes, including reduced vitamin content, while total polyphenols, flavonoids, and antioxidant activity remained stable. Microbiological quality was acceptable over a period of 12 weeks but high RH during storage deteriorated sensory attributes. Liang leaves showed promise of being a functional food ingredient.